The analysis of kinematical characteristics in taekwondo roundhouse kick - Kinoshita, M.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to analyze the kinematical characteristics of lower torso and kicking leg in Taekwondo roundhouse kick (RHK), which was characterized by kicking speed and continuous kicking. The results were summarized as follows: 1) The kicking speed pattern was similar between the two subjects at 90% time of RHK. 2) One subject produced kicking speed mainly by the movements of hip joint and knee joint, while the other by the movements of lower torso and knee joint. 3) The movement of lower torso for the latter subject had a larger range of motion than the other, which had the disadvantage for the continuous kicking. Thus, RHK techniques for both kicking speed and continuous kicking are influenced by the presence of whipping like motion which is characterized by the limited lower torso movement and the faster movement of lower limb joints.